2015
DOI: 10.5604/17322693.1164430
|View full text |Cite
|
Sign up to set email alerts
|

Vascular access in diabetic patients. Are these patients “difficult”?

Abstract: Diabetics with stage V chronic kidney disease (CKD) on hemodialysis (HD) are considered as "difficult patients", because of problems with creation of the vascular access. There is controversy regarding the results and recommendations for preparation of the vascular access in these patients. The aim of this retrospective study was to evaluate the results of creating different types of arteriovenous fistula (AVFs) in consecutive series of patients starting dialysis treatment. The analysis was performed in 741 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…On account of atherosclerosis exists more often and severe in diabetes patients, there is a wide range of vascular lesions, making it difficult to establish a vascular access [ 28 ]. In addition, diabetes is often accompanied by hyperlipemia, hypoalbuminemia, and high blood coagulation, which also lead to AVF’s obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On account of atherosclerosis exists more often and severe in diabetes patients, there is a wide range of vascular lesions, making it difficult to establish a vascular access [ 28 ]. In addition, diabetes is often accompanied by hyperlipemia, hypoalbuminemia, and high blood coagulation, which also lead to AVF’s obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated atherosclerotic changes in forearm arteries in diabetic patients appear in 60% of hemodialysis patients [ 28 ]. It is possible to create a native AVF in 90% of diabetic patients, although this requires more procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is a common comorbidity associated with ESRD and, consequently, many patients on dialysis have diabetes as well [ 10 ]. Due to the deleterious effects that diabetes has on vascular anatomy, fistula creation becomes more difficult and is not always possible.…”
Section: Discussionmentioning
confidence: 99%
“…(Yan Y, et al, 2018). Beberapa penelitian lain menunjukkan perubahan aterosklerotik pada arteri lengan bawah pada pasien diabetes muncul pada 60% pasien hemodialysis (Gołębiowski, et al, 2015).…”
Section: Pendahuluanunclassified